THE ROLE AND SIGNIFICANCE OF CARDIAC MAGNETIC RESONANCE IN HYPERTROPHIC CARDIOMIOPATHY - Nedeljkovic Arsenovic, Olga; Bjelica, Teodora; Tesic, Milorad; Nedeljkovic, Ivana; Tomic, Ana; Mladenovic Markovic, Ana; Maksimovic, Ruzica (Medical Research, 2025)
Introduction: Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disorder of cardiomyocytes that leads to myocardial thickening. Aims: The aims of this study were to establish the diagnosis of HCM in patients with hypertrophic left ventricle walls, to evaluate myocardial tissue, and to assess the degree of myocardial fibrosis using cardiac magnetic resonance (CMR).Material and Methods: The study included 51 patients diagnosed with HCM by CMR (27 males, 24 females) and was carried out in the University Clinical Centre of Serbia, Center of Radiology. All collected patient data was obtained from official medical documentation for this retrospective observational study. CMR confirmed HCM in 51 pts based on a standard imaging protocol performed on a 1.5T Siemens scanner, with the contrast agent Gadolinium. Regarding Late Gadolinium Enhancement (LGE) distribution, CMR enables the detection of focal fibrosis and helps to differentiate the etiology of the hypertrophied myocardium.Results: Left ventricular outflow tract obstruction was observed in 9 (17.6%) patients. Asymmetric HCM was noted in 41 (80.4%) patients. LGE presence was detected in 39 (76.5%) patients, most notably in the septal region (62.7%). The degree of fibrosis was estimated at a median of 6% of the left ventricular mass and a median of 11 grams of fibrosis per gram of left ventricular mass. Conclusion: CMR as a non-invasive method represents the gold standard for myocardial tissue characterization. The detection of myocardial fibrosis, a major trigger for the development of malignant arrhythmias, positions CMR as a risk stratification method in HCM patients.
Keywords: hypertrophic cardiomyopathy; cardiac magnetic resonance; late gadolinium enhancement; degree of fibrosis; arrhythmias.